Discussion of "A Framework to Evaluate the Benefit of Seismic Upgrading". Issue 3 (August 2019) - Galanis, Panagiotis; Broccardo, Marco; Bodenmann, Lukas; Stojadinović, Božidar
Discussers (Michel et al.) address the paper "A Framework to Evaluate the Benefit of Seismic Upgrading" written by the coauthors of this response. Discussers present the compliance factor approach to evaluate existing structures and determine the need for a seismic upgrade implemented in the Swiss code SIA 269/8 and compare this approach to the one presented in the discussed paper. The approach proposed in the discussed paper combines elements of the Pacific Earthquake Engineering Research (PEER) Center Performance-Based Earthquake Engineering (PBEE) framework and the standard actuarial frequency-severity approach. Discussers criticize this approach as not being risk based and, consequently, consider it inappropriate for seismic evaluation of existing buildings. Coauthors welcome the comparison of different approaches for evaluation of existing buildings but disagree with the discussers' characterization of the PEER PBEE framework and, by extension, the approach of the discussed paper.